2011
DOI: 10.35196/rfm.2011.1.63
|View full text |Cite
|
Sign up to set email alerts
|

CALIDAD POSTCOSECHA DE FRUTOS DE PITAHAYA (Hylocereus undatus Haw.) COSECHADOS EN TRES ESTADOS DE MADUREZ

Abstract: En este estudio se evaluó la calidad postcosecha de frutos de pitahaya (Hylocereus undatus Haw.) cosechados en tres estados de madurez: inicial, medio y completo, con 25-50, 50-75 y 75-100 % de color rojo en la cáscara, respectivamente. Los frutos fueron almacenados a 20 ± 2 °C. Se evaluaron características físicas y químicas durante 12 d y las fisiológicas por 8 d. La pérdida de peso al concluir el almacenamiento fue mayor (P ≤ 0.05) en frutos de madurez inicial (7.8 %) que con madurez media (6.1 %) y complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 7 publications
2
4
0
3
Order By: Relevance
“…Because the CF.DF -1 of BRS Minipitaya do Cerrado, BRS Lua do Cerrado and BRS Luz do Cerrado fruits were close to 1.5, their fruits were a little more elongated (Table 1). These results were similar to the ones observed by other authors, who also classified the S. undatus fruits as slightly oblong (CHIK et al, 2011;TRAN e YEN, 2014;OSUNA-ENCISO et al, 2016;PATWARY et al, 2013) The largest CF.DF -1 ratio was found in BRS Âmbar do Cerrado fruits (1.96 in the 2019/2020 cycle and 1.83 in the 2020/2021 cycle) presenting fruits typically ovoid (Table 1). These data corroborate with he reported by Chik et al (2011) 2).…”
Section: Sibut Et Al (2023)supporting
confidence: 90%
“…Because the CF.DF -1 of BRS Minipitaya do Cerrado, BRS Lua do Cerrado and BRS Luz do Cerrado fruits were close to 1.5, their fruits were a little more elongated (Table 1). These results were similar to the ones observed by other authors, who also classified the S. undatus fruits as slightly oblong (CHIK et al, 2011;TRAN e YEN, 2014;OSUNA-ENCISO et al, 2016;PATWARY et al, 2013) The largest CF.DF -1 ratio was found in BRS Âmbar do Cerrado fruits (1.96 in the 2019/2020 cycle and 1.83 in the 2020/2021 cycle) presenting fruits typically ovoid (Table 1). These data corroborate with he reported by Chik et al (2011) 2).…”
Section: Sibut Et Al (2023)supporting
confidence: 90%
“…However, Chitarra and Chitarra (2005) recommend caution in establishing this relationship because insipid fruits, containing low levels of soluble solids and acids, present high ratios, which can lead to erroneous interpretations of quality. As reported by Osuna Enciso et al (2011), the increase in the ratio of pitaya fruits is due to the drastic reduction in titratable acidity, not an indicator of quality since soluble solids do not increase. Martínez (2011) andCenturión Yah et al (2008) also observed that the increase in the ratio was due to the decrease in acidity.…”
Section: Physiological Maturity Of Pitaya Fruitsmentioning
confidence: 64%
“…The soluble solids content is dependent on the maturation stage and generally increases during maturation evolution through biosynthesis or degradation of polysaccharides (Chitarra and Chitarra, 2005). Some authors evaluated the soluble solids content in pitaya fruits and observed an increase in this variable with the advancement of maturation, obtaining ripe fruits with 12.2 ºBrix (Ortiz and Takahashi, 2015) and 13.6 ºBrix (Osuna Enciso et al, 2011). Other authors, when evaluating different pitaya genetic materials, reported values from 10.9 to 14.1 ºBrix (Castillo- Martínez et al, 2005), 14.5 to 17.6 ºBrix (Martínez, 2011), 12.0 to 16.0 ºBrix (Livera-Muñoz et al, 2010) and 16.0 to 17.0 ºBrix .…”
Section: Physiological Maturity Of Pitaya Fruitsmentioning
confidence: 99%
“…To identify if dragonfruit varieties in homegardens may have had an extended reproductive phenology, data on the frequency of flower and fruit production in the Yucatan state were compared to those reported for commercial/industrial plantations of H. undatus in other Mexican states (Castillo-Martínez and Ortiz-Hernandez 1994; Martínez-Ruiz et al 2017; Osuna-Enciso et al 2016). The results of the management practices interviews were compared to those obtained from a similar survey of Campeche homegardens (Manzanero-Acevedo et al 2014).…”
Section: Study Sitementioning
confidence: 99%